Suwar al-Kawakib: Bridging Greek and Islamic Astronomy in the History of Islamic Astronomy - Fatimah Nur Aliyah; Ahmad Izzuddin (Astroislamica: Journal of Islamic Astronomy, 2026)
This study examines the classical text Suwar al-Kawakib al-Thabitah by Abd al-Rahman al-Sufi, a tenth-century Islamic scholar who bridged Greek and Islamic astronomy. The work's influence spread throughout Europe from the tenth to the nineteenth century in three successive waves: its translation in Andalusia, its adoption into Renaissance star atlases such as the Uranometria, and its role in the standardization of modern international star catalogues. Using a historical method, this research traces the contribution of Suwar al-Kawakib to cosmology, Arabic star nomenclature, and astronomical observation, through which Islamic science became integrated into global scientific standards. The research employs a qualitative approach, applying historical analysis to examine the role of al-Sufi's Suwar al-Kawakib in the development of Greek and Islamic astronomy. Primary data consist of the original text, its translations, and literature related to the constellations. These data are analyzed to understand the work's impact from the tenth to the nineteenth century, including the integration of astronomy and astrology, star nomenclature, and observational methodology, in order to clarify the role of Islamic astronomy in shaping international scientific standards. The findings show that Suwar al-Kawakib not only advanced Islamic cosmology but also played a key role in establishing star-naming conventions that remain in use today. Al-Sufi's contribution extends beyond astronomy to include cultural knowledge that facilitated the transmission of learning between the Islamic world and the West. The book underscores the significance of Islamic astronomy's influence on the development of global astronomy and on the international scientific standards now widely recognized.